The deletion between Chomsky and Imam AlKhudari in AlKhudari,s footnote in light of the transformative generative theory (Sebha University Conference Proceedings, 2024)
This paper seeks to shed light on the comparison between deletion in the transformative generative theory, and between deletion according to grammarians, in general, and according to the Imam. Al-Khudari in particular, and an attempt to identify the most prominent points of difference and similarity between them. It can also be said that Imam Al-Khudari and Chomsky adopted the rational approach in analysis and induction, but the transformative generative theory cannot be fully applied in the Arabic manner, perhaps because of the methodological problems and its subsequent developments, and that the 1965 model is the model closest to the ideas of the traditional Arab theory, etc. Subsequent amendments only developed them, and the comparison was made through the tree representation of a number of examples in Al-Khudari’s footnote to Ibn Aqeel’s explanation. Appending to that tree is the elements mentioned in the example of the transformative generative theory)